Flavor enhancers and/or Vitamin C in growing-finishing rations - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1977)
Supplemental vitamin C fed at two different levels (550 or 1,100mg, per kg, of diet) did not improve animal performance at the swine research center. Adding apple flavor or sodium bicarbonate did not change results.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Flavor enhancers; Vitamin C; Growing-finishing rations